2019
DOI: 10.1108/mhrj-12-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Being known, branching out: troupes, teams and recovery

Abstract: Purpose The purpose of this paper is to reach beyond existing research into the mental health benefits of arts-based or educational opportunities, to discover the particular impact on members’ recovery processes of being part of a committed, long-term troupe or community – specifically focussing on specialist theatre companies. Design/methodology/approach Following a literature review investigating the growing number of theatre troupes for mental health service users, qualitative research was conducted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…For example, community arts provide an opportunity to interact with other people with SMI in a non-judgemental setting, enabling self-comparisons to occur without stigma. The current findings found that positive interactions helped to validate the self, which mirrors the process of internalisation within the Social Identity Approach to Health (Best et al, 2016;Haslam et al, 2018;Heinemeyer & Rowe, 2019;Williams et al, 2018). The arts activity also provided an alternative shared experience away from SMI, which allows individuals to compare themselves with others through a different, and often positive, lens.…”
Section: Discussionmentioning
confidence: 58%
“…For example, community arts provide an opportunity to interact with other people with SMI in a non-judgemental setting, enabling self-comparisons to occur without stigma. The current findings found that positive interactions helped to validate the self, which mirrors the process of internalisation within the Social Identity Approach to Health (Best et al, 2016;Haslam et al, 2018;Heinemeyer & Rowe, 2019;Williams et al, 2018). The arts activity also provided an alternative shared experience away from SMI, which allows individuals to compare themselves with others through a different, and often positive, lens.…”
Section: Discussionmentioning
confidence: 58%